Home Languages and Home Learning: Creativity (Portuguese version) - Devitt, Ann; LaMorgia, Francesca (TCD Youtube Channel, 2020)
Short video (Portuguese version) for parents of multilingual families to support young children being creative.
Keywords: multilingualism; creativity; family learning; Family Digital Literacy